Długofalowy wzrost gospodarczy jako fundament stabilności politycznej państwa - Dokurno, Zbigniew (The Long-Range Economic Growth as a Fundament for Political Stability of Countries, 2007)
The economic sense of the economic growth is very common. It is one of the main problems in the history of economic thought. Both its premises and essence have changed. It implies the searching of new sources economies' growth and redefines it towards the sustainable development. This redefinition of the economic growth paradigm is strictly related with political programme of modern states. Then the political programme changes with the change of state's definition. The main purpose of the article is an attempt to define an essence of modern state, premises of its political programme and terms of political stability in the context of modified economic growth paradigm.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 195-207